Indeginous knowledge sytems and environmental management in Zimbabwe: case of Bikita south - Mawanza, Precious (Midlands Sate University, 2015)
This study was carried out in Bikita South District in Masvingo Province of Zimbabwe. The purpose of the study was to examine the effectiveness of Indigenous Knowledge Systems (IKS) in environmental management in Bikita South. Targeted population were drawn from Bikita South ward 2 from the traditional leadership of the area, Agriculture extension officer and the general populace using qualitative research method through purposive sampling and snowball. The research found out that the district has got a variety of IKS which are being practised leading to good environmental conservation in the District. The research found out that the use of IKS in environmental management is being hindered by a number of challenges including differences in religious beliefs, lack of integration among the community members, greediness of traditional leaders, lack of participation on among community members in traditional gatherings, negligence, poverty, poor documentation among others in addition to a negative perception of IKS revealed by the community members. This has negatively affected the effectiveness of IKS in environmental management in Bikita South. Suggested solutions or recommendations to the challenges faced through the use of IKS in environmental management include that of the establishment of community libraries, modern and traditional environmental management approaches to be integrated together ,diversify the economy of the District, reduction of population pressure in rural areas through the creation of jobs in towns ,educate the young generation on the importance of IKS and the concept of IKS be a compulsory module or subject to be taught at primary and tertiary learning levels among others.